Prospects of virtual or computational towing tank facility for the shipbuilding industry of Bangladesh (Journal of Naval Architecture and Marine Engineering, 2014)
Shipbuilding is on the verge of blooming into the major foreign revenue-earning industry in Bangladesh. A number of export-oriented shipyards are developed to deliver different kinds of ships for local and international clients. For designing a ship, model testing facilities are required not only to predict power requirements but also to evaluate its performance in actual sea operation. At present, Bangladesh does not have this facility. Also carrying out model testing is very expensive and time consuming. Therefore, now-a-days most of the shipyards all over the world are using virtual or computational towing tank facility. Due to improvement of solution algorithm for handling non-linear problem and computational infrastructure, computational or virtual towing tank can be used as a replacement of physical towing tank experiments. In the present study, a numerical or computational towing tank technique named WISDAM which is developed at The University of Tokyo, Japan is described with its applicability in perspective of Bangladesh shipbuilding industries.DOI: http://dx.doi.org/10.3329/jname.v11i1.15619